COMMUNICATIVE LANGUAGE TEACHING AND ITS MISCONCEPTIONS ABOUT THE PRACTICE IN ENGLISH LANGUAGE TEACHING (ELT) - Diana, Sri (Universitas Pendidikan Indonesia, 2014)
Communicative Language Teaching (CLT) has been accepted as one of the teaching methods by numerous language teachers due to its major focus on developing learners’ communicative competence. This paper aims to describe communicative language teaching, misinterpretations about its practice and the factors leading to teachers’ misconceptions. It shows four misinterpreted beliefs of the implementation of communicative language teaching: communicative skills, teacher’s role in communicative activities, fluency and accuracy as the main goals and teaching techniques. It then presents three reasons that might lead to teachers’ misinterpretations concerning the practice of CLT. Teachers do not have enough training and adequate resources.